Electric Field Evaluation Using the Finite Element Method and Proxy Models for the Design of Stator Slots in a Permanent Magnet Synchronous Motor - Stéfano Frizzo Stefenon (Electronics, 2020)
The efficiency of electric motors is being improved every day and projects with design variations can improve their performance. Among electric motors, the Permanent Magnet Synchronous Machine (PMSM) is being increasingly used, because of its growing use in electric vehicles. Simulating design variations using the Finite Element Method (FEM) can improve PMSM design, and by optimizing the parameters based on the FEM, even better results can be achieved. The design of the PMSM stator slots must be evaluated, as conductors are accommodated and an electrical potential is applied at this location. The FEM parameters are varied, and the results can be used to build an approximate model, known as a proxy model. The proxy model can then be used in a mathematical programming problem to optimize the design of stators that have less electric field in certain regions, thus reducing the chance of developing a failure. The results of the proposed methodology show that its application is promising for machine design and can also be used for the design of other systems.